Strategic factors on interpreting remanufacturing quality- Certifying framework to address warranty aftermarket for Malaysian industry - N, Mohamed; M.Z.M, Saman; S, Sharif; H.S., Hamzah (IOP Publishing, 2018)
While the concept of remanufacturing is gaining popularity globally, literature and theory on strategic decision-making on certifying for warranty in this area remain limited. A strategic and establish concept flow is developed based on extensive literature review and surveys with experienced experts who are dealing with remanufactured, reconditioned, rebuilt and reused components. The remanufacturing research on evaluating quality assurance of remanufactured component targets macro-level parameters and the indicators which must be confirmed for evaluation. The strategic remanufacturing factors identified from the literature review are discussed in a brainstorming session with a number of remanufacturing researchers and academic experts. The study is further broadened by industrial surveys and case studies to justify the inputs on developing a framework to certify remanufactured components. Preliminary results have established the key factors of remanufacturing quality control that might lead to the strict quality assurance of remanufactured components. Later, the developed framework can be used as a benchmarking tool to certify remanufactured components and warranty issuance. The findings serve as the foundation for further research concerning Original Equipment Manufacturer (OEM) or Original Equipment Remanufacturer (OER) and Independent Equipment Remanufacturer (IER) in the Malaysian Remanufacturing Industry.